A QCM‐D and SAXS Study of the Interaction of Functionalised Lyotropic Liquid Crystalline Lipid Nanoparticles with siRNA. (3rd April 2017) - Tajik‐Ahmadabad, Behnoosh; Mechler, Adam; Muir, Benjamin W.; McLean, Keith; Hinton, Tracey M.; Separovic, Frances; Polyzos, Anastasios
Abstract: Biophysical studies were undertaken to investigate the binding and release of short interfering ribonucleic acid (siRNA) from lyotropic liquid crystalline lipid nanoparticles (LNPs) by using a quartz crystal microbalance (QCM). These carriers are based on phytantriol (Phy) and the cationic lipid DOTAP (1, 2‐dioleoyloxy‐3‐(trimethylammonium)propane). The nonlamellar phase LNPs were tethered to the surface of the QCM chip for analysis based on biotin–neutravidin binding, which enabled the controlled deposition of siRNA–LNP complexes with different lipid/siRNA charge ratios on a QCM‐D crystal sensor. The binding and release of biomolecules such as siRNA from LNPs was demonstrated to be reliably characterised by this technique. Essential physicochemical parameters of the cationic LNP/siRNA lipoplexes—such as particle size, lyotropic phase behaviour, cytotoxicity, gene silencing and uptake efficiency—were also assessed. The SAXS data show that when the pH was lowered to 5.5 the structure of the lipoplexes did not change, thus indicating that the acidic conditions of the endosome were not a significant factor in the release of siRNA from the cationic lipidic carriers. Abstract : Releasing siRNA : Binding and release of short interfering ribonucleic acid (siRNA) from lyotropic liquid crystalline lipid nanoparticles (LNPs) on a self‐assembled monolayer was demonstrated by using the aid of a quartz crystal microbalance. Small‐angle X‐ray scattering (SAXS) was used to characterise the attached LNPs.